Digital business transformation how established companies sustain competitive advantage from now to next - Vaz, Nigel (John Wiley & Sons, Inc., 2021)
"Digital business transformation is a hot topic, and Publicis Sapient has been helping to digitally transform clients? businesses for 30 years. This book explains how to combine strategy, experience, engineering, data, and agile to produce stronger digital business outcomes. The book will include examples of the challenges faced by globally respected organizations to determine if they are going to defend, differentiate or disrupt themselves and understand which approach will yield successful outcomes, in the short medium and longer term and how leaders can de-construct decision-making across every level of an organization once they embark on this journey"